Trauma Kandung Kemih Ekstraperitoneal Tak Teridentifikasi: Kasus dengan Sistografi Normal: Laporan Kasus - Affandi, Reza; Azmi, Yufi Aulia; Wirjopranoto, Soetojo (Cermin Dunia Kedokteran, 2025)
Introduction: Bladder trauma is the second most commonly injured organ in the genitourinary system after the kidney. The injury can be caused by a variety of mechanisms, including blunt trauma, penetrating trauma, and iatrogenic procedures. Case: A 21-year-old male with multiple injuries following a motorbike accident. Upon examination, a foreign body was detected in the right thigh. A CT scan revealed a metal rod impaled in the patient’s bladder without any contrast leakage. The patient was planned for foreign body removal and bladder repair. During the removal, bladder leakage was detected. The patient underwent foreign body removal and bladder repair. Discussion: This case underscores the importance of considering bladder injury in trauma patients, even in the absence of classic clinical signs such as haematuria. It also highlights the potential limitations of initial imaging techniques like cystography in detecting bladder injuries when foreign bodies are present. Conclusion: This case emphasizes the importance of maintaining a high index of suspicion and considering intraoperative exploration or additional diagnostic methods when imaging findings are inconclusive. Revising the diagnostic protocol for trauma patients with suspected bladder injury, especially if a foreign body is present, is essential to avoid missed diagnoses and improve patient outcomes.